STUDY OF PHYSICOCHEMICAL PARAMETERS FOR CADMIUM (II) AND MERCURY (II) PHYTOREMEDIATION USING THE SPECIE Eichhornia crassipes (WATER HYACINTH) - Poma Llantoy, Víctor Raúl (2014)
In this work, the studies were performed to measure the sorption capacity of metal ions Cd (II) and Hg (II) using the specie Eichhornia crassipes (water hyacinth). This study includes assays where the nutrient concentration, the pH and the metal ion concentration were optimized. This tests were carried out at room temperature and with aqueous solutions of Cd (II), Hg (II), in which the samples of Eichhornia crassipes were placed. To confirm the removal of these metals, the waste solutions after the treatment with the Water Hyacinth species were treated using the method APHA 3030-e. However, Eichhornia crassipes samples were treated using the EPA 200.3 method. The concentration of Cd (II) was determined by a ICP-OES spectrometer and Hg (II), by an atomic absorption spectrophotometer. The results showed: Optimal dosage 1 mL of A and 0,5 mL of B, optimum pH 5, optimum concentration of Cd (II) and Hg (II) 5 mg / L for each ion. With these parameters, it was started the removal of 5 mg / L of the metal ions contained in 1 L of solution. Being the percentages of sorption 16,56% for Cd (II) and 15,6% for Hg (II) after a period of 7 days.